2018
DOI: 10.1002/lary.27105
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Role of Bile Acids in Acquired Laryngotracheal Stenosis

Abstract: NA. Laryngoscope, 128:2029-2033, 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 33 publications
2
24
1
Order By: Relevance
“…The present examination of the potential for pepsin to contribute to fibrosis in iSGS was therefore important for informing current treatment strategies. Whereas the findings herein do not support a role for pepsin in EMT in the larynx, previous findings suggest that acid‐targeting medical therapies may allow ongoing damage by other nonacid reflux components, warranting further investigation …”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…The present examination of the potential for pepsin to contribute to fibrosis in iSGS was therefore important for informing current treatment strategies. Whereas the findings herein do not support a role for pepsin in EMT in the larynx, previous findings suggest that acid‐targeting medical therapies may allow ongoing damage by other nonacid reflux components, warranting further investigation …”
Section: Discussioncontrasting
confidence: 86%
“…Anti‐reflux medical therapy has demonstrated success independently or as an adjunct to surgical treatment . Physiologically, relevant concentrations of bile acids induce markers of EMT in human primary tracheal epithelial cells, demonstrating a potential role for refluxed bile acids in tracheal scarring and remodeling and thus in stenosis …”
Section: Introductionmentioning
confidence: 99%
“…The examination was normal, and no subglottic pathology was encountered. However, these symptoms could be due to laryngopharyngeal reflux, which has been shown to alter laryngeal cell phenotype . The samples had to be obtained during general anesthesia due to the difficulty in accessing the subglottis; therefore, it was not possible to access subglottic samples from completely asymptomatic patients (who would not be undergoing this procedure).…”
Section: Discussionmentioning
confidence: 99%
“…The current survey reveals similar lack of awareness of the potential role of LPR in development of laryngotracheal stenosis and chronic media otitis, despite an increasing literature which supports this relationship. 10,11,26,27 Surprisingly, non-laryngologists seem to be unaware about the role of LPR in bronchial diseases such as asthma; however, many studies have demonstrated that LPR is involved in the development of bronchial hypersensitivity conditions, such as asthma, 28,29 or chronic obstructive pulmonary disease. 30 In the current survey, the largest differences between laryngologists and non-laryngologists concern diagnostic approach towards LPR, particularly with regard to examinations such as esophagoscopy and MII-pH.…”
Section: Discussionmentioning
confidence: 99%